Ethnomathematics Contained of Guided Inquiry for Elementary School Fourth Grade Student (Universitas Negeri Semarang, 2019)
The purpose of this study was to develop learning tool of Guided Inquiry learning model, in term of Ethnomathematics contained validity, effectiveness, and practicability of the learning model. The design of this study is Research and Development (R&D) from Thiagarajan with 4D, namely define, design, develop and dissemination, at the define step which is to find the problem of low mathematical values, at this design stage planning syllabus, lesson plans, learning devices are designed. At the development stage the author combine mathematics and Cirebon culture in a learning tools, and than final stage dissemination learning tools. Limited trial of learning device is conducted in SDN 1 Kalitengah, trial design is using Pretest-Posttest Control Group Design. SDN 2 Kalitengah is as experimental class and SDN 3 Kalitengah as control class. The technique of collecting data in this study is with test technique and non-test technique. Non-test technique in this study is using observation method, documentation, and questionnaire. The instrument of study is observation sheet, validity sheet of learning device of Guided Inquiry contained Ethnomathematics. The technique of analyzing data is using pre-requirement test (validity test, reliability test, different power, difficulty level, normality test, and homogeneity test), N-gain test, and independent sample t test. The result of study, learning device that is developed categorized valid to be used with score result on the average lesson plan (RPP) 3.35, Syllabus 3.46, teaching materials 3.43, student work sheet (LKS) 3.37 and study result test 3.49. The result of effectiveness of learning device shows progress of mean of study result before applying in number 61.97 and after applying in number of 89.72, N-gain score of experimental class in number of 0.73.